Antioxidant Activity of Musa Paradisiaca (Banana) Soft Pith and Its Cytotoxicity Against Oral Squamous Carcinoma Cell Lines - Siti Aisyah Abd Ghafar; Ira Hazwani Hasan Fikri; Zolkapli Eshak (Universiti Sains Islam Malaysia, 2024)
Musa paradisiaca also known as banana possess great medicinal value such as haematopoietic, immunomodulatory, antifungal, anti-diabetic and antioxidant effects. Antioxidant and antiproliferative activities between two different species, banana soft pith (BSP) Awak and Abu were conducted in this study. Briefly, BSP were collected (Baling, Kedah) and extracted by 70% ethanol forming crude extract. The crude extracts were then fractionated by n-hexane, ethyl acetate, butanol and water. All BSP extracts and fractions were subjected to total phenolic content (TPC), total flavonoid content (TFC), 2,2-diphenyl-1-picrylhydrazil (DPPH) free radical scavenging assay, ferric reducing antioxidant potential (FRAP) assay and cytotoxic assay screening (MTT). Fraction ethyl acetate from BSP Abu showed the highest cytotoxic activity towards HSC-4 cell lines (26.95 ± 1.80 µg/mL) and the highest TPC (12.25 ± 0.39 mg GAE/g) and FRAP assay (191.03 ± 0.83 mg FeSO4/g) values as compared to other fractions among BSP Abu. However, TPC (13.93 ± 0.28 mg GAE/g) and TFC (441.59 ± 19.31 mg QE/g) values of BSP Awak were found to be higher as compared to BSP Abu.